Gambaran Kondisi Gingiva Berdasarkan Jenis Kelamin pada Siswa-Siswi SMPN 1 Lubuk Sikaping Kanagarian Pauh Kecamatan Lubuk Sikaping Kabupaten Pasaman Timur - Annisa Monifa Rahmah; Syukra Alhamda (Jurnal Kesehatan Cendikia Jenius, 2023)
Dental and oral health problems are often encountered in Indonesian society, especially in teenage boys and girls. This study aims to determine the description of gingival conditions based on gender in students at SMPN 1 Kanagarian Pauh, Lubuk Suhuing District, East Pasaman Regency. This research uses a "descriptive" method. The population of this study was all students of SMPN 1 Kanagarian Pauh, Lubuk Suhuing District, East Pasaman Regency. The sampling technique was "simple random sampling" of 100 people. Data collection through direct examination. Data analysis used univariate analysis, namely data analysis carried out on one research variable in the form of frequency distribution tabulation. The results of this study show that the frequency distribution based on gender is that male students are more likely to have healthy gingiva conditions at 60% compared to female students at 34%. The conclusion of the research shows that based on gender among students at SMPN 1 Lubuk Suhuing Kanagarian Pauh, Lubuk Suhuing District, East Pasaman Regency, what is most often found in male students is healthy gingival conditions and in female students what is most often found is inflammation. light. It is recommended that students brush their teeth twice a day, namely after breakfast and at night before bed, consume vegetables and fruit and have their teeth checked by a dental health service at least once every 6 months.